Lepra Bubalorum, a Potential Reservoir of Mycobacterium leprae - Faber, William R.; Menke, Henk; Rutten, Victor; Pieters, Toine (Frontiers in Microbiology, 2021)
In 1926, a mycobacterial skin disease was observed in water buffaloes by researchers in Indonesia. The disease was designated as skin tuberculosis, though it was hypothesized that it might be a form of leprosy or a leprosy-like disease. In a follow-up study (Ph.D. thesis Lobel, 1934, Utrecht University, Netherlands) a similar nodular skin disease was described in Indonesian water buffaloes and named “lepra bubalorum” or “nodular leprosy.” Two decades later Kraneveld and Roza (1954) reported that, so far, the diagnosis lepra bubalorum had been made in 146 cases in Indonesia. After a final series of research reports by Indonesian veterinarians in 1961, no subsequent cases were published. Based on information from these reports, it can be concluded that, even though evidence of nerve involvement in buffaloes was not reported, similarities exist between lepra bubalorum and Hansen’s disease (leprosy), i.e., nodular skin lesions with a chronic course and microscopically granulomatous reactions with AFB in globi in vacuoles. This raises the question as to whether these historical cases might indeed have been caused by Mycobacterium leprae, Mycobacterium lepromatosis or another representative of the M. leprae complex. The future use of state-of-the-art molecular techniques may answer this question and may also help to answer the question whether water buffaloes should be considered as a potential natural reservoir of the causative pathogen of Hansen’s disease.